2007
DOI: 10.1111/j.1475-097x.2007.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency QRS electrocardiogram

Abstract: The standard 12-lead electrocardiogram (ECG) is one of the most commonly used methods for diagnosing heart disease. Standard ECG is not always optimal, however, and new ECG methods can provide additional information. Analysis of high-frequency QRS components (HF-QRS) has been shown to increase the diagnostic performance of the ECG. Several investigators have studied HF-QRS in different cardiac conditions, including acute myocardial ischaemia and myocardial infarction, but more knowledge is needed about the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Abboud [34] showed that a bandpass 150-250 Hz reveals a zone of reduced amplitude in high-frequency QRS complex during acute occlusion of the coronary artery. A substantial body of evidence exists regarding the usefulness of a 150-250Hz bandpass, summarized in the review by Tragardh and Schlegel [35]. …”
Section: Relative Value Of Various Qrs Frequenciesmentioning
confidence: 99%
“…Abboud [34] showed that a bandpass 150-250 Hz reveals a zone of reduced amplitude in high-frequency QRS complex during acute occlusion of the coronary artery. A substantial body of evidence exists regarding the usefulness of a 150-250Hz bandpass, summarized in the review by Tragardh and Schlegel [35]. …”
Section: Relative Value Of Various Qrs Frequenciesmentioning
confidence: 99%
“…Preserving frequencies with large magnitudes makes the original and augmented data look alike, but the core information for solving the task might disappear. For instance, detecting abnormalities in the Electrocardiogram (ECG) signals relies on capturing the pattern of small high-frequency components (Tragardh and Schlegel 2006), whereas the magnitude spectrum P mag eliminates the core frequencies for the classification during the data augmentation process just because those have a small magnitude.…”
Section: Magnitude Spectrummentioning
confidence: 99%
“…В основе ЭРМ лежат изменения ряда наиболее важных электрофизиологических феноменов [10]. В клинической практике эти феномены получают отражение при дифференцированной электрокардиографии (ЭКГ) скорость активации, реполяризации, дисперсия и гетерогенность, [8,11] и при оценке данных ЭКГ высокого разрешения [12].…”
Section: ишемическая болезнь сердцаunclassified